The disguised testis: a rare case of intra-abdominal seminoma presenting as a lower abdominal mass - Ranga, Hansraj; Vaishnavi; Sharma, Luv; Singla, Rajveer; Yadav , Dushyant Kumar (International Surgery Journal, 2025)
Intra-abdominal undescended testes in adults are rare and often present as abdominal or pelvic masses, leading to diagnostic confusion with neoplasms such as gastrointestinal stromal tumors (GIST). Unrecognized cryptorchidism carries a significant risk of malignant transformation, particularly into germ cell tumors. Thorough clinical assessment, including genital examination, remains essential in such cases. A 55 years old male presented with progressive lower abdominal pain and a firm, non-tender mass in the left iliac fossa. There was no prior history of undescended testis or related surgery. Imaging studies, including contrast-enhanced CT, suggested a well-defined mass near the sigmoid colon, initially suspected to be a GIST. The patient underwent exploratory laparotomy for definitive diagnosis and management. Intraoperatively, a well-encapsulated, 6 cm mass was identified adjacent to the sigmoid colon. The lesion was excised completely without bowel involvement. Histopathological analysis revealed atrophic testicular tissue with intratubular germ cell neoplasia (ITGCN), confirming the mass as an intra-abdominal undescended testis with pre-malignant changes. This case highlights the diagnostic challenge posed by intra-abdominal undescended testes in adults. Awareness of this rare presentation, combined with careful genital examination, is crucial to avoid misdiagnosis and unnecessary extensive resections. Cryptorchidism should always be considered in the differential diagnosis of unexplained abdominal masses in males, regardless of age.